ARTIFICIAL INTELLIGENCE AND AUTOMATION: A LITERATURE REVIEW ON BUSINESS ADAPTATION AND RESILIENCE - Loso Judijanto; Alim Hardiansyah; Al-Amin (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The use of artificial intelligence (AI) and automation in the business world has become a major focus in the literature addressing business adaptation and resilience. This study reviews the literature to explore how AI and automation technologies can be applied to improve operational efficiency, respond quickly to market changes, and manage supply chains and human resources more effectively. The results of this study show that AI and automation can not only optimise business processes by reducing costs and human error, but can also improve a company's ability to anticipate and cope with disruptions and crisis situations. As such, the integration of AI and automation gives companies a significant competitive advantage, enabling better adaptation to changing business environments and improving overall resilience.